New water-soluble Ruthenium(II) cytotoxic complex: biological activity and celular distribution - Morais, Tânia S. (2015)
A novel water soluble organometallic compound, [RuCp(mTPPMSNa)(2,2'-bipy)][CF3SO3] (TM85, where Cp=eta(5)-cyclopentadienyl, mTPPMS = diphenylphosphane-benzene-3-sulfonate and 2,2'-bipy = 2,2'-bipyridine) is presented herein. Studies of interactions with relevant proteins were performed to understand the behavior and mode of action of this complex in the biological environment. Electrochemical and fluorescence studies showed that TM85 strongly binds to albumin. Studies carried out to study the formation of TM85 which adducts with ubiquitin and cytochrome c were performed by electrospray ionization mass spectrometry (ESI-MS). Antitumor activity was evaluated against a variety of human cancer cell lines, namely A2780, A2780cisR, MCF7, MDAMB231, HT29, PC3 and V79 non-tumorigenic cells and compared with the reference drug cisplatin. TM85 cytotoxic effect was reduced in the presence of endocytosis modulators at low temperatures, suggesting an energy-dependent mechanism consistent with endocytosis. Ultrastructural analysis by transmission electron microscopy (TEM) revealed that TM85 targets the endomembranar system disrupting the Golgi and also affects the mitochondria. Disruption of plasma membrane observed by flow cytometry could lead to cellular damage and cell death. On the whole, the biological activity evaluated herein combined with the water solubility property suggests that complex TM85 could be a promising anticancer agent. (C) 2013 Elsevier Inc. All rights reserved.